The Spirituality and Wholeness in Education - Mulalić, Muhidin (Journal of History Culture and Art Research, 2017)
The modern materialistic worldview has influenced educational institutions to emphasize more on inculcating students with skills and knowledge to the neglect of the students’ values and virtues. Consequently, education is a commodity, shaped according to the market. Education, influenced by the market, neglects a comprehensive approach and students’ intellectual, physical and cultural needs. Market’s preference for the technical and natural sciences contributed towards the creation of the mechanical conception of education. The market also influenced the institutions of higher learning to neglect the role of humanities and social sciences. The humanity is also at the break of the ecological, nuclear, chemical and biological crisis, terrorism, moral degeneration, and there is increasing disregard for culture, tradition, and values. These challenges raised questions about outcomes of modern education. Since such education could not balance and fulfill students’ material, intellectual and cultural needs; therefore, this paper examines how the holistic learning and teaching can pave the way towards the 21st-century education model.